Ubiquitous Information Technologies and Applications CUTE 2013 - Jeong, Young-Sik.; Park, Young-Ho.; Hsu, Ching-Hsien (Robert).; Park, James J. (Jong Hyuk).; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The theme of CUTE is focused on the various aspects of ubiquitous computing for advances in ubiquitous computing and provides an opportunity for academic and industry professionals to discuss the latest issues and progress in the area of ubiquitous computing. Therefore this book will be include the various theories and practical applications in ubiquitous computing
Ubiquitous Communication and Networking -- Ubiquitous Software Technology -- Ubiquitous Systems and Applications -- Ubiquitous Security, Privacy and Trust.
Keywords: Engineering; Computer Communication Networks; Multimedia systems; Telecommunication; Engineering; Communications Engineering, Networks; Computer Communication Networks; Multimedia Information Systems